Du rite de consécration en littérature : Apollinaire et Césaire, entre tradition et modernité - Malela, Buata B. (Romanica Silesiana)
The paper focuses on the notion of ritual in literary works by Guillaume Apollinaire and Aimé Césaire. It applies the sociology of literature as an interpretive tool which emphasizes the function and social significance of rituals. Every writer who wishes to become popular has to undergo a ritual of consecration, which involves the employment of a literary strategy, and the understanding of the literary game and the institutions involved. In the case of Apollinaire and Césaire this means the consideration of several universes and time frames. This constraint then pushes them to reformulate the problems of literary tradition and modernity. Key words: Rite, French literature, Apollinaire, Aimé Césaire, Modernity